Designing for naturalistic decision-making - Hare, Chrisminder (2017)
Emergencies are safety critical situations where decision-makers make rapid and quick decisions. It is essential that decision-makers maintain a high level of performance whilst resolving the incident. Knowledge of human factors influences on decision-maker performance is critical to understand when designing technologies to support naturalistic decision-making.